The Competency of English Language Teachers in Implementing the English Language Literacy Programme - Abdul Wahid, Suhaimi; Mohd Yusof, Sanitah; Azean Atan, Noor; Ibrahim, Halijah (International Journal of Psychosocial Rehabilitation, 2020)
The teachers’ competency level was investigated from four related aspects, which are knowledge competency, teaching skills competency, assessment and evaluation competency, and professional values and behavior competency. A total of 141 English language literacy teachers from 83 primary schools in Pontian, Johor, were involved with this study. The research design is through the use of a questionnaire, which is intended to measure the competency level of respondents. Data that had been collected is analyzed with Statistical Package for the Social Sciences (SPSS 12.0) to find the mean, frequency, and standard deviation. ANOVA and t-tests were used to analyze the hypothesis. The findings showed that the level of competency is high for the knowledge, teaching skills, assessment and evaluation, and professional values and behavior aspects. As for the hypothesis, there are no significant differences in the competency of the English language teachers across the school zones, teaching experience, and gender factors. Implications of the study were discussed, which were then followed by a few proposals of the study to the stakeholders, such as English teachers that are involved with the LINUS Bahasa Inggeris (LBI) program, the school administrators, local education authorities (District Education Office and the State Education Department), and the Ministry of Education.